Adipokines as biomarkers of postpartum subclinical endometritis in dairy cows. Issue 3 (September 2020) - Pereira, Gonçalo; Bexiga, Ricardo; Chagas e Silva, João; Silva, Elisabete; Ramé, Christelle; Dupont, Joëlle; Guo, Yongzhi; Humblot, Patrice; Lopes-da-Costa, Luís
Abstract : Adipokines emerged as regulators of metabolism and inflammation in several scenarios. This study evaluated the relationship between adipokines (adiponectin, chemerin and visfatin) and cytological (subclinical) endometritis, by comparing healthy (without), transient (recovered by 45 days postpartum (DPP)) and persistent (until 45 DPP) endometritis cows ( n  = 49). Cows with persistent endometritis had higher adiponectin concentrations in plasma (at 21 DPP, P  < 0.05 and at 45 DPP, P  < 0.01) and in uterine fluid (at 45 DPP, P  < 0.001), and higher chemerin concentrations in plasma ( P  < 0.05) and uterine fluid ( P  < 0.01) at 45 DPP than healthy cows. Cows with persistent endometritis had higher gene transcription in the cellular pellet of uterine fluid and protein expression in the endometrium of these adipokines and their receptors than healthy cows. Adiponectin plasma concentrations allowed to discriminate healthy from persistent endometritis cows, in 87% (21 DPP) and 98% (45 DPP) of cases, and adiponectin and chemerin uterine fluid concentrations at 45 DPP allowed for this discrimination in 100% of cases. Cows with concentrations above the cutoff were a minimum of 3.5 (plasma 21 DPP), 20.4 (plasma 45 DPP), and 33.3 (uterine fluid 45 DPP) times more at risk of evidencing persistent endometritis at 45 DPP than cows with concentrations below the cutoff. Overall, results indicate a relationship between adipokine signalling and the inflammatory status of the postpartum uterus of dairy cows, evidencing that adipokines represent suitable biomarkers of subclinical endometritis, able to predict the risk of persistence of inflammation.